1967
DOI: 10.1002/jez.1401650209
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between prolactin and thyroid hormone in amphibian development

Abstract: Tadpoles were treated with intraperitoneal injections of mammalian prolactin and growth hormone (NIH). The growth rate of hwophysectomied tad. poles (R. pipiens) was accelerated by both hormones, prolactin having the greater effect. Metamorphosis in the bullfrog ( R . catesbeiuna) was inhibited by prolactin but not by growth hormone. The results are interpreted to indicate a general antag. onism between prolactin and thyroid hormone in amphibian development with respect to both growth rate and metamorphosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1
1

Year Published

1967
1967
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(23 citation statements)
references
References 8 publications
3
18
1
1
Order By: Relevance
“…The possibility suggests itself that we are dealing with a substance of goitrogenic properties. Support for the possibility of goitrogenicity of prolactin is provided by our earlier experiments (10) in which normal bullfrog tadpoles treated with prolactin entered into metamorphic stasis and yet their thyroids reached a high level of activation as judged by histological criteria. This evidence was indicative of a goitrogen-like effect since prolactin had induced activation of the gland without a physiological indication of release of active hormone.…”
Section: Discussionmentioning
confidence: 94%
“…The possibility suggests itself that we are dealing with a substance of goitrogenic properties. Support for the possibility of goitrogenicity of prolactin is provided by our earlier experiments (10) in which normal bullfrog tadpoles treated with prolactin entered into metamorphic stasis and yet their thyroids reached a high level of activation as judged by histological criteria. This evidence was indicative of a goitrogen-like effect since prolactin had induced activation of the gland without a physiological indication of release of active hormone.…”
Section: Discussionmentioning
confidence: 94%
“…It has also been reported that mammalian PRL counteracts the effects of TH when added to cultured tadpole tissues (5,6). These observations have led to a widely held belief that PRL has the biological role of a ''juvenile'' hormone in amphibian metamorphosis (7,8). It was predicted that the levels of endogenous PRL, just like that of JH in insects, should be high at premetamorphosis and prometamorphosis stages and then drop at the climax of metamorphosis (7).…”
mentioning
confidence: 99%
“…These observations have led to a widely held belief that PRL has the biological role of a ''juvenile'' hormone in amphibian metamorphosis (7,8). It was predicted that the levels of endogenous PRL, just like that of JH in insects, should be high at premetamorphosis and prometamorphosis stages and then drop at the climax of metamorphosis (7). However, the direct measurements of both endogenous PRL mRNA (9,10) and protein levels of PRL in the serum (11,12) showed them to be low at premetamorphosis and prometamorphosis stages rising substantially only at the climax of metamorphosis, a result that does not support a juvenilizing role for endogenous PRL.…”
mentioning
confidence: 99%
“…However, the results do not indicate whether the differences between the capacities of these grafts to inhibit the action of thyroxine results from quantitative and/or qualitiative changes in the glands. At a first glance it would appear that the results of these experiments do not support the bihormonal model of meta-326 A. DERBY morphosis proposed by Etkin and Gona, 1967, in which prolactin activity is highest during premetamorphosis and decreases during prometamorphosis to a minimum at climax. However, before such a judgment can be made the following point should be considered.…”
Section: Derby and Etkin ('68) Demonstrated That A Pituitary Implantmentioning
confidence: 56%